2000
DOI: 10.1002/1521-4095(200012)12:24<1959::aid-adma1959>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adhesion at Poly(ethylene glycol) Modified Surfaces

Abstract: The inhibition of protein adsorption to the surfaces of biomedical devices is a crucial requirement for avoiding implant‐associated infections or thrombus formation on blood‐contacting artificial surfaces and thus for increasing the long‐term biocompatibility of the devices. Here, the use of surface plasmon resonance and scanning force microscopy using protein‐modified tips (see figure) to study protein adhesion on poly(ethylene glycol) (PEG) grafted polymer materials is discussed. The PEG‐rafted materials are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Snellings et al [663] found reduced adhesion of human serum albumin (HSA) coated tips to surfaces coated with PEG polymer brushes. Force-distance curves with a Si 3 N 4 tip (uncoated or coated with polypropylene or fibrinogen) on PMMA intraocular lenses (used for surgical replacement of natural lenses) with and without hyaluronan coating were studied by Casinelli et al [664] in 0.1 M NaCl.…”
Section: Adhesion In Mems and Proteinsmentioning
confidence: 99%
“…Snellings et al [663] found reduced adhesion of human serum albumin (HSA) coated tips to surfaces coated with PEG polymer brushes. Force-distance curves with a Si 3 N 4 tip (uncoated or coated with polypropylene or fibrinogen) on PMMA intraocular lenses (used for surgical replacement of natural lenses) with and without hyaluronan coating were studied by Casinelli et al [664] in 0.1 M NaCl.…”
Section: Adhesion In Mems and Proteinsmentioning
confidence: 99%
“…The ability of these materials to inhibit protein adsorption and therefore reduce biofouling has been known for decades [125]. Other related polymers are also being explored to minimize protein adsorption.…”
Section: ) Surface Immobilized Polymersmentioning
confidence: 99%
“…From literature it is known that coating with polyethylene glycol (PEG) makes a surface more antiadhesive [56]. Furthermore is was reported that bound PEG whiskers induce more ordered α-helix in BSA [56,57] and that ethylene glycol as a solvent in comparison to water results in formation of intermolecular β-sheets in IgG [58].…”
Section: Influence Of Surface Modificationmentioning
confidence: 99%